PENGARUH MEDIA HIRAGANA GOI KARUTA TERHADAP PENGUASAAN KOSAKATA BAHASA JEPANG SISWA - Veziah agustia Surianda; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Vocabulary is something that must be mastered in order to communicate well and correctly. Based on observations during educational field practice (PLK) at SMAN 1 Koto Therefore, the solution given to overcome the problem of low student motivation and vocabulary is by using hiragana goi karuta media. The research is purpose to reveal the hiragana goi karuta media effect on students' vocabulary mastery in learning Japanese. This research included in quantitative research. This method for research is an method in experimental in the shape of a Quasi Experiment (quasi experiment). The design used in this research was a one group pretest posttest design through sample of 35 people. From the hypothesis test found in the paired sample t-test results, so the conclusion that H0 was rejected and H1 was accepted at a level of significant is 0.05, because the sig value <0.05 (0.000<0.05) which means there is a significant difference from the pretest value results. and posttest. So, the conclusion the use of hiragana goi karuta media is effective in mastering the vocabulary of students at SMAN 1 Koto XI Tarusan.